Hospital-Level COVID-19 Preparedness and Crisis Management in Czechia - Petr Michenka; David Marx (Frontiers Media S.A., 2023)
Objectives: The COVID-19 pandemic exposed the inadequacy of pandemic preparedness mechanisms worldwide. This study gathered comprehensive data from Czech hospitals, identified possible weaknesses in important areas of crisis preparedness, and quantified changes performed to enhance crisis resilience of healthcare facilities.Methods: Drawing on literature review on pandemic preparedness and hospital crisis management and detailed interviews with hospital representatives, a questionnaire was designed and distributed by email among quality managers of all Czech hospitals. Statistical analysis of their responses was conducted using EZR software. Fisher's exact test and Kruskal-Wallis test, with post hoc testing, were used to assess statistical significance.Results: Achieving response rate of 31.9%, responses from 65 hospitals were analysed. New crisis management policies were necessary in 72.3% of responding hospitals. Furthermore, a majority of the respondents changes indicated the need for changes in policies on general pandemic, human resources and infrastructure and material preparedness.Conclusion: The COVID-19 crisis required significant alterations to previously established hospital crisis management protocols and establishment of new ones. The absence of a unified system for crisis preparedness was noted at hospital and national levels.